Carneiro, Roberto; Toscano, Juan Carlos; Díaz, Tamara (2012). Los desafíos de las TIC para el cambio educativo. Madrid: OEI-Fundación Santillana. - Bartolomé Pina., Antonio R. (Revista Fuentes, 2013)
Carneiro, Roberto; Toscano, Juan Carlos; Díaz, Tamara (2012). Los desafíos de las TIC para el cambio educativo. Madrid: OEI-Fundación Santillana.